PERSPEKTYWA FEMINISTYCZNA W BADANIACH NA TEMAT ZBIOROWYCH STOSUNKÓW PRACY - Kubisa, Julia (Wydział Prawa i Administracji UAM, 2008)
A feminist perspective in the research on collective industrial relations relates to the division of work in respect of gender and the differentiation between productive and reproductive work, conditioning the situation of men and women on the labour market and in trade unions. Therefore, a feminist perspective is a valuable complementation of the studies on industrial relations. It identifies other reasons for men and women to join the unions and the women’s types o f union activity that have been so far neglected. While the role for women has been traditionally confined to housework, the men’s roles in trade unions have been perceived as “male” or “manly” activities. A feminist perspective also points out to other aspects that are noteworthy, such as unequal pay for work of the same value or unpaid housework, and their influence of women’s activity in trade unions. The paper is an overview o f the literature on a feminist perspective in the research into collective industrial relations.
A FEMINIST PERSPECTIVE IN THE RESEARCH ON COLLECTIVE INDUSTRIAL RELATIONS